Regulation and Warning Determination with Food Labelling in Controlling Consumption Patterns - Nur Siyam; Miranda Gita Wahyuningtyas; Herlina Tri Damailia; Sri Achadi Nugraheni (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
An unhealthy lifestyle can increase people's risk of developing non-communicable diseases. Obesity, Hypertension, and Diabetes Mellitus are metabolic disorders suffered by people who at the end of this decade attack younger age groups. So, it is important to immediately get handling from the government. For this reason, the government needs to realize policies in the form of stipulating regulations in controlling the consumption of unhealthy products through effective methods. The purpose of the study is to review the effectiveness of regulations and warnings with food labeling in controlling consumption patterns. The systematic review approach of literature review with PRISMA searches for articles in three databases: PubMed, Scopus, and ScienceDirect. Ten articles were selected through several stages of screening and underwent quality assessment. According to the findings of the study, the establishment of government/stakeholder regulations in related sectors and warnings with food labeling with increased food literacy can increase the effectiveness of controlling the consumption of unhealthy products sustainably. Food labeling needs to emphasize information related to healthy or unhealthy products to consume.